Security and Privacy in Social Networks - Altshuler, Yaniv; Elovici, Yuval; Cremers, Armin B.; Aharony, Nadav; Pentland, Alex.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Security and Privacy in Social Networks brings to the forefront innovative approaches for analyzing and enhancing the security and privacy dimensions in online social networks, and is the first comprehensive attempt dedicated entirely to this field. In order to facilitate the transition of such methods from theory to mechanisms designed and deployed in existing online social networking services, the book aspires to create a common language between the researchers and practitioners of this new area- spanning from the theory of computational social sciences to conventional security and network engineering.
Introduction to Security and Privacy in Social Networks -- Interdisciplinary Impact Analysis of Privacy in Social Networks -- Recognizing Your Digital Friends -- Encryption for Peer-to-Peer Social Networks -- Crowdsourcing and Ethics -- The Effect of Social Status on Decision-Making and Prices in Financial Networks -- Stealing Reality: When Criminals Become Data Scientists (or Vice Versa) -- Applications of k-Anonymity and ℓ-Diversity in Publishing Online Social Networks -- Links Reconstruction Attack -- An Analysis of Anonymity in the Bitcoin System -- Privacy-Preserving Data Integration using Decoupled Data.
Keywords: Computer communication systems; Computer security; Application software; Computer Communication Networks; Systems and Data Security; Information Systems Applications (incl. Internet).